Acoustic Doppler current profiler observations of migration patternsof zooplankton in the Cretan Sea - Emmanuel Potiris; Constantin Frangoulis; Alkiviadis Kalampokis; Manolis Ntoumas; Manos Pettas; George Petihakis; Vassilis Zervakis (Ocean Science, 2018)
The lack of knowledge of the mesopelagic layer inhabitants, especially those performing strong vertical migration, is an acknowledged challenge. This incomplete representation leads to the exclusion of an active carbon and nutrient pathway from the surface to the deeper layers and vice versa. The vertical migration of mesopelagic inhabitants (macroplanktonic and micronektonic) was observed by acoustical means for almost 2.5 years in the epipelagic and mesopelagic layers of the open oligotrophic Cretan Sea (south Aegean Sea, eastern Mediterranean) at the site of an operational fixed-point observatory located at 1500 m depth. The observed organisms were categorized into four groups according to their migration patterns. The variability of the migration patterns was inspected in relation to the physical and biological environmental conditions of the study area. The stratification of the water column does not act as a barrier for the vertical motion of the strongest migrants that move up to 400 m every day. Instead, changes in light intensity (lunar cycle, daylight duration, cloudiness) and the presence of prey and predators seem to explain the observed daily, monthly and seasonal variability. The continuous presence of these organisms, which are capable of vertical motion despite the profound circulation variability at the site of the observatory, implies their presence in the broader study area. The fundamental implications of the above regarding biogeochemical processing in oligotrophic seas due to the intimate link between the carbon (C) and nutrient cycles, are discussed.